TRANSFORMASI KESULTANAN BANJAR DI ERA DIGITAL - Mira Ayudia Sari; Fadhel Muhammad (Yayasan Haiah Nusratul Islam, 2025)
Social media has transformed how identities and authority are represented in digital spaces. This study examines how the Sultanate of Banjar, which lost political power after its dissolution by the Dutch in 1905, employs Instagram as a medium for cultural representation and identity negotiation. Using a qualitative approach through literature review and document analysis of the official account @kesultananbanjar_official, the research applies representation theory, identity negotiation, and Reading Images Grammar of Visual Design as its framework. Findings reveal that the Sultanate revitalizes heritage through visual content, historical narratives, and hashtags such as #KesultananBanjar. By integrating religion, tradition, and mysticism, the account strengthens cultural identity and fosters interaction via likes, views, and collaborations. Ultimately, social media becomes a strategic arena for the Sultanate to preserve heritage, assert symbolic power, and expand cultural presence globally.